PERBANDINGAN METODE JUS DAN PARUT PADA LABU SIAM UNTUK MENURUNKAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Hariyadi; Nata Waskita, Kuncara; Susilowati (Universitas Cokroaminoto Palopo, 2025)
The aim of this research is to identify a comparison of the juice and grated methods of chayote to reduce blood pressure in hypertension sufferers. The research uses experimental methods with Quasy Experimental and a Two Group Pre Test-Post Test With Out Control Group Design approach. The sampling technique used Non Probability Sampling with a total of 32 respondents with hypertension who were divided into two treatment groups. The Wilcoxcon test results of giving the chayote juice method for 7 days obtained p = 0.000 (0.05) and when giving the chayote juice grated method for 7 days obtained p = 0.000 (0.05), meaning that there was a change in blood pressure before and after giving the method. juice and grate for 7 days. The results of the Mann-Whitney test comparing two groups showed that the systolic value was p = 0.035 (0.05) and the diastolic value was p = 0.030 (0.05), meaning that there was a difference in the comparison of the juice and grated methods of chayote for 7 days on changes in blood pressure. Giving chayote juice is effective in lowering blood pressure in hypertension sufferers, but not all respondents fell into the normal blood pressure value category, due to poor food consumption patterns. Researchers hope that chayote juice can be an alternative to lowering blood pressure in hypertension sufferers.